FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI POLITIK MAHASISWA UKSW ASAL SUMATERA UTARA BATAK TOBA DALAM PEMILU (PILPRES) TAHUN 2024 - Rouli; Nani Mediatati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors that influence the political participation of WSSW students from North Sumatra Batak Toba in the 2024 presidential election. This research uses a qualitative approach with data collection techniques through interviews and documentation of 50 student respondents. The results showed that the level of student political participation was still low, only 11 people (22%) of respondents used their voting rights and 39 people (78%) did not use their voting rights in the 2024 presidential election. Internal factors that influence political participation include political knowledge, individual interests, and political awareness. Meanwhile, external factors that influence are the friendship environment, social media, and socialization of presidential elections from the campus. Internal factors such as political awareness and knowledge, as well as external factors such as social environment and election socialization, encourage students to participate more. In contrast, individual interests and the friendship environment are the main factors for students to participate. This study recommends the need for increased socialization, political education, and social environmental support to increase student political participation in the next election.